Respuesta :

Answer:

Midpoint of AB              = (0 + 2a / 2 , 0 + 0 / 2) = (2a / 2 , 0 / 2) = (a,0)

x coordinate of point c = a

                                  N = (0 + a / 2 , 0 + b / 2) = (a / 2 , b / 2)

                                  M = ( 2a + a / 2 , 0 + b / 2) = (3a / 2 , b / 2)

                                MA = √(3a / 2 - 0)² + b / 2 - 0)²

                                       = √(3a / 2 )² + (b / 2) = 9a² / 4 + b² / 4

                                NB = √(a / 2 - 2a)² + (b / 2 - 0 )²

                                      = √( a / 2 - 4a / 2)² + (b / 2 - 0)²

                                      = √(-3a / 2)² + (b / 2)² = √9a² / 4 + b² / 4

Step-by-step explanation:

I tried my best hope its correct :0

ACCESS MORE